AN ANALYSIS OF TEACHERS’ TALK IN TEACHING ENGLISH ON VIRTUAL CLASS AT MTs MUHAMMADIYAH TOLITOLI - Moh. Firmansyah; Mohammad Rafi’I Mohammad Sata (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research is aimed to find out the teachers’ talk in teaching English on virtual class at MTs Muhammadiyah Tolitoli. This study uses a qualitative descriptive. The researcher using theory FLINT (Foreign Language Interaction) by Brown H.D (2007) which leads to Indirect Influence and Direct Influence. The research sample were two (2) teachers who teach English at MTs Muhammadiyah Tolitoli. The techniques for collecting data were Interview and Documentation and analyzed using Miles & Huberman theory. The results of this study shows that teachers’ talk divided into 2, namely Direct Influence are consists of giving information, correcting, gives directions, Criticizes, and Indirect Influence are consists of deal with feelings, praises or encourages, uses students idea, ask questions, and learning through virtual classes at MTs Muhammadiyah has implemented all teacher talk by Brown. These teachers’ talk Have been applied but less than optimal due to problems regarding the network from students and teachers themselves Keywords: Teachers’ Talk, Foreign Language Interaction.